PERSONAL CHARACTERISTICS OF GIFTED YOUNGSTERS - Arakelyan , M. A.; Grigoryan , V. H. (Արդի հոգեբանություն, 2018)
The number of studies on giftedness rapidly increased at the end of the last century, characterizing the giftedness mainly as a cognitive capability, high level of intellectual abilities. Despite of numerous studies, we know a little about the personal characteristics of gifted youngsters, which are important for revealing and realizing the potential of these people. More than 500 high school students were diagnosed, during which 35 gifted youngsters were identified. Further studies showed significant differences of the personal peculiarities of gifted youngsters and difficulties in regulating the emotional sphere.